Economic and Legal Aspects of Compensation for Environmental Damage - AFANASIEVA, Olga Romanovna; ZARAPINA, Lidia Vladimirovna; MUKHLYNINA, Maria Mikhailovna; ADAMENKO, Alla Petrovna; SHUMAKOV, Sergey Aleksandrovich (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.v11.3(43).03, 2020)
The article considers the economic and legal aspects of compensation for environmental damage. The variety of consequences that occur as a result of environmental offenses, the complex structure of environmental damage, and specific objects of environmental legal relations determine the necessity to apply environmental legal, as well as civil, norms to the regulation of relations on compensation for environmental damage. Interaction, convergence, and interpenetration of social relations lead to the strengthening of integration processes of their legal mediation. The necessity of complete dissociation of norms of environmental and civil legislation, especially as regards the regulation of the considered relations, can hardly be accepted. Ecologized norms appear, the inclusion of which in various normative legal acts is connected with the economic development of countries, threat of ecological crisis, complication of public relations, and the necessity to consider the laws of nature.